PEMBERDAYAAN POLITIK PEMILIH MUDA DI DESA SESETAN MENUJU PILKADA SERENTAK TAHUN 2024 - Nurak, Anastacia Patricia Novlina; Adhinata, Bayu; Wijaya, Chintiya Meydayanti (LPPM Universitas Flores, 2024)
The political empowerment program aims to increase public awareness of politics, particularly for first-time voters in the 2024 simultaneous regional elections in Sesetan village, South Denpasar district, Bali province. Political empowerment focuses on efforts carried out by those with access, to information, and the capability to formulate policies for others who must be involved in the implementation of those policies. Political education is the key to empowering young voters, particularly those belonging to Generation Z (Gen Z). The method used in this community service involves several stages, consisting of three phases: preparation, implementation, and evaluation. The preparation phase includes problem identification, determination of empowerment targets, coordination with internship partners, and implementation planning. The implementation phase involves pre-test data collection, the execution of political empowerment activities, and post-test data collection following the political empowerment. The evaluation phase includes activity evaluation based on the pre-test and post-test results, the development of frameworks suitable for the empowerment targets, and the preparation of output frameworks to be provided to partners capable of implementing these frameworks. Two main issues were identified: the low awareness of participating in electoral activities such as becoming election supervisors, and the lack of political knowledge about distinguishing political hoaxes related to elections. The findings revealed that the low participation awareness is due to the lack of exposure to informal political education outside of formal education, as well as the minimal literacy education on how to utilise gadgets to select reliable sources of political information.